Mantle Plumes: A Multidisciplinary Approach - Ritter, Joachim Roland Reinmar; Christensen, Ulrich R. (Springer-Verlag Berlin Heidelberg, 2007)
The concept of mantle plumes, hot buoyant rock masses that rise in the mantle, is a key to understand intraplate volcanism in the framework of modern plate tectonics. Recent progress in instrumental, analytical and satellite technology enables scientists to verify the plume hypothesis with seismic tomography, isotope geochemistry and other sophisticated techniques. A group of experts review these advances in plume research, and present a general overview on recent plume studies.
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Magmatismus; Vulkanismus; Island; Zentralmassiv; Frankreich; Hawaii; Hotspot; Böhmen; Vogtland; Eifel; Deutschland; Manteldiapir